Understanding the Relationship Between Learning Motivation and Science Process Skills in Biology Learning: A Correlational Study - Susanti, Tri Suci; Antika, Linda Tri (Indonesian Journal of Biology Education, 2025)
This study was based on the importance of motivation as an internal factor that influences student engagement in learning, particularly in developing science process skills, which are central to the scientific learning approach. Lack of self-motivation shows that students are less active in learning activities. This study aimed to determine the correlation between learning motivation and students' science process skills. This research used the Guided Inquiry model to enhance learning motivation and science process skills. The subjects of this study were students class X-A of Islamic boarding school in Pamekasan in 2023/2024 academic year with 23 students. This research was a correlational study with regression correlation analysis techniques. Data collection on learning motivation used ARCS (Attention, Relevance, Confidence, and Satisfaction) motivation questionnaire, while science process skills used a rubric. The results of this study indicated that there was a significant relationship between learning motivation and science process skills. The regression analysis results showed a large R value of 0.647 which indicated that there was high relationship between learning motivation and science process skills. The findings indicated that an increase in students’ learning motivation was associated with an improvement in their science process skills. Guided Inquiry learning model can be a recommended model in empowering students' learning motivation and science process skills, especially in biology learning.